CURRICULUM IMPLEMENTATI ON DUAL TRACK IN PROGRESS STUDENT COMPETENCIES AT SMA NEGERI 1 SANGATTA SELATAN - Pratomo, Danu; Komariyah, Laili; Bahzar, Moh. (Pena Cendekia Insani, 2026)
Improving the competency of students who do not continue their education after graduation is a crucial need to prepare them to enter the workforce or become entrepreneurs. School data shows that 34% of graduates of SMA Negeri 1 Sangatta Selatan do not continue their education. This study aims to describe the principal's management in planning, organizing, implementing, and supervising the dual-track curriculum. The study used a qualitative approach with a case study method. Data were collected through observation, interviews, and documentation, then analyzed using the Miles and Huberman interactive model. The results showed that program planning was carried out collaboratively and based on student needs with a flexible schedule, organization through a clear team structure according to competencies, implementation through theoretical and practical learning using the 3P method in the fields of fashion design, culinary design, make-up, and multimedia, as well as continuous supervision and monitoring. The implementation of the dual-track curriculum has proven effective in improving student competency as a provision for work and entrepreneurship and has the potential to be developed in schools with similar characteristics.